A repercussão da BNCC na cidade de Sorocaba /SP à luz das teorias pedagógicas - Freitas, Carlos Augusto Amaro de (2020)
Abstract: the present work was developed under the methodological guidance of bibliographic, documentary and field research. Researching Brazilian education in times of change that guide its practice towards training people for the job market under the bias of a neo-technical education, the foundation of the common national curriculum base, was the research proposal, the specific focus was the municipality of Sorocaba / SP. The curriculum, in its historicity, and the BNCC were analyzed from the critical and non-critical pedagogical theories, to better understand the relationships behind the political, economic, cultural and social orientations that imposed the construction and approval of the national base. Despite its recent existence as a public policy for the implementation of a nationally guiding curriculum for education networks in Brazilian states and municipalities, we undertook a field survey to verify in loco, among professionals of the Sorocaba school space (managers, coordinators and teachers) , responsible for teaching in their formal curricular guidelines, as the base has been shaping the school in Sorocaba since its approval. Considering the short time since the base was approved, it was found to be insipid in its presence in the schools surveyed, including the lack of knowledge of BNCC as a curriculum advisor among the research subjects. We conclude that, in spite of the changes imposed on education, transforming it more and more into merchandise, there are perspectives and pedagogical orientations that face and keeps on the horizon the possibility of a transformative education that allows to increase the humanization potential of the people involved in the educational process, which proved to be forceful in the process of formulating the base, denouncing its real intentions.